Histopathological examination and transcriptomic profiling reveal gossypol toxicity-responsive genes related to fertility in mice - Mehari, Teame Gereziher; Jiang, Maorong; Gu, Dandan; Qian, Jiaxi; Tang, Jungfeng; Wubshet, Ashenafi Kiros; Fang, Hui; Wang, Kai; Yao, Deng-Bing; Wang, Baohua (Frontiers in Pharmacology, 2025)
IntroductionGossypol impairs reproduction in both sexes, inducing mitochondrial dysfunction, irregular cycles, and fewer ovarian follicles, leading to decreased fertility rates. The present investigation was undertaken to evaluate the toxicological effects of (+)-gossypol powder, a substance derived from cottonseed in mice.MethodsThe mice were divided into four groups: a control group receiving pure dimethyl sulfoxide (DMSO) and three treatment groups receiving 20, 40, or 80 mg/kg gossypol dissolved in DMSO. The mice were treated daily via oral gavage for 14 days and subjected to clinical observation. At study completion, physical, hematological, and histopathological (ovary, testis, liver, lung, kidney, and spleen) evaluations were performed.ResultsCompared with the control treatment, gossypol treatment adversely affected routine blood parameters and histopathology (p < 0.05). Routine blood tests revealed significantly elevated neutrophil granulocytes and monocytes, along with a marked decrease in lymphocytes. Furthermore, gossypol treatment inhibited spermatogenesis, caused follicular degeneration in the ovaries, and induced tissue damage in the liver, kidney, lung, and spleen. Furthermore, transcriptome sequencing of ovaries, testes, and livers from mice treated with DMSO or 80 mg/kg gossypol was performed to investigate the molecular mechanisms of reproductive damage. Eighteen cDNA libraries were constructed and yielded 113.6 Gb of raw reads, which were filtered to obtain 112.4 Gb of high-quality clean reads. The analysis identified 639 differentially expressed genes (DEGs). Consecutively, weighted gene coexpression network analysis (WGCNA) revealed a strong correlation between the blue module hub gene ENSMUSG00000048138 (Dmrt2) and mouse blood test results. Dmrt2 gene expression was confirmed by RT-qPCR and GFP expression analysis. Lentivirus-mediated DMRT2 silencing (shRNA-Sh-a, Sh-b, and Sh-c) resulted in low DMRT2 expression, whereas overexpression (OE-DMRT2) resulted in high DMRT2 expression relative to that of the controls. Gossypol stress significantly upregulated Dmrt2 expression in ovarian tissue.ConclusionGossypol powder from cotton is toxic to mice, affecting their pathology, histology, and hematology. This study strongly links the Dmrt2 gene in reproductive tissues to gossypol resistance, highlighting its potential protective role and advancing the understanding of gene regulation in mouse fertility. Further research and food safety considerations are therefore crucial.